2015
DOI: 10.1017/jns.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Depression and serum 25-hydroxyvitamin D in older adults living at northern latitudes – AGES-Reykjavik Study

Abstract: Low vitamin D status may be associated with depression. Few studies have examined vitamin D and depression in older adults living at northern latitudes. The present study cross-sectionally investigated serum 25-hydroxyvitamin D (25(OH)D) status and depression among 5006 community-dwelling older persons (66–96 years) living in Iceland (latitudes 64–66°N). Depressive symptoms were measured by the fifteen-item Geriatric Depression Scale (GDS-15). Current major depressive disorder was assessed according to Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…Nearly two thirds of the patients had 25OHD below the threshold of 50 nmol/L. Considering previous Icelandic studies on vitamin D, it shows that in our participants there was a similar or somewhat higher prevalence of inadequate 25OHD (60 %) as compared to community dwelling old adults (41–50 %) [ 26 ], geriatric hospitalized patients (56 %) [ 27 ] and young adults (61 %) [ 28 ]. Considering this low intake of dairy products along with low 25OHD levels, more supervision and education/guidance to the patients seems to be of importance in order to reduce the risk osteoporosis can be considered as beneficial.…”
Section: Discussionsupporting
confidence: 58%
“…Nearly two thirds of the patients had 25OHD below the threshold of 50 nmol/L. Considering previous Icelandic studies on vitamin D, it shows that in our participants there was a similar or somewhat higher prevalence of inadequate 25OHD (60 %) as compared to community dwelling old adults (41–50 %) [ 26 ], geriatric hospitalized patients (56 %) [ 27 ] and young adults (61 %) [ 28 ]. Considering this low intake of dairy products along with low 25OHD levels, more supervision and education/guidance to the patients seems to be of importance in order to reduce the risk osteoporosis can be considered as beneficial.…”
Section: Discussionsupporting
confidence: 58%
“…) and that men with low vitamin D levels (<30 nmol/l) were twice as likely to be depressed as men with levels above 50 nmol/l (Imai et al . ).…”
Section: First Findings Of Moodfoodmentioning
confidence: 97%
“…The Netherlands 2981 Dutch Persons with depression and/or anxiety disorder (n = 2329) and controls (n = 652) 18-65 2004-2007 2005-2008, 2006-2009, 2008-2011, 2010-2013, 2013-2016 35-55 1985-1994 1989-1990, 1991-1993, 1995-1996, 1997-1998, 2001, 2002-2004, 2006, 2007-2009, 2011(pilot), 2012-2013, 2015-2016 20-102 1998-2000 2001-2003, 2004-2006, 2007-2009, 2013- in vegetables, olive oil, wholegrains, fruit, fish and moderate in wine and red and processed meat) might be protective against depressive symptoms (Vermeulen et al 2016) and that men with low vitamin D levels (<30 nmol/l) were twice as likely to be depressed as men with levels above 50 nmol/l (Imai et al 2015). Cohort analyses on the relation of obesity with depression revealed that over a 6-year period both elevated BMI and waist circumference moderately increased the odds of developing a major depressive disorder (by 17%) and that compared to healthy controls, current major depressive disorder patients have greater odds of either gaining or losing weight over a 2-year period, regardless of antidepressant use (Gibson-Smith et al 2015).…”
Section: First Findings Of Moodfoodmentioning
confidence: 99%
“…Paired-samples t-tests were performed to assess whether changes over time in 25 The associations between change in 25(OH)D and change in depressive symptoms over 13 or 6 years were analysed by multivariable linear regression analysis. Based on previous studies on 25(OH)D and depression (11,14,15,24), sex was examined as a potential effect modifier. Another potential effect modifier was baseline serum 25(OH)D concentration, as this may influence the change in serum 25(OH)D (45).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In many crosssectional studies, lower 25(OH)D concentrations were associated with a higher risk of depressive symptoms or depression (e.g. (10,11)), while in others, vitamin D and depression were not associated (12,13). Prospective studies showed a higher incidence of depressive symptoms or depression over 1-6 years in older persons who had low baseline vitamin D levels (14,15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%